Dioxygen reactivity of new bispidine-copper complexes - Comba, Peter; Haaf, Christina Melanie; Helmle, Stefan; Pandian, Shanthi; Waleska, Arkadius (Inorganic chemistry, 2012)
The reactivity of copper complexes of three different second-generation bispidine-based ligands (bispidine = 3,7-diazabicyclo[3.3.1]nonane; mono- and bis-tetradentate; exclusively tertiary amine donors) with dioxygen [(reversible) binding of dioxygen by copper(I)] is reported. The UV-vis, electrospray ionization mass spectrometry, electron paramagnetic resonance, and vibrational spectra (resonance Raman) of the dioxygen adducts indicate that, depending on the ligand and reaction conditions, several different species (mono- and dinuclear, superoxo, peroxo, and hydroperoxo), partially in equilibrium with each other, are formed. Minor changes in the ligand structure and/or experimental conditions (solvent, temperature, relative concentrations) allow switching between the different forms. With one of the ligands, an end-on peroxodicopper(II) complex and a mononuclear hydroperoxocopper(II) complex could be characterized. With another ligand, reversible dioxygen binding was observed, leading to a metastable superoxocopper(II) complex. The amount of dioxygen involved in the reversible binding to CuI was determined quantitatively. The mechanism of dioxygen binding as well as the preference of each of the three ligands for a particular dioxygen adduct is discussed on the basis of a computational (density functional theory) analysis.